Radioimmunotherapy: a game-changer for advanced non-small cell lung cancer - Xue, Huichan; Chen, Yunshang; Zhou, Yun (Frontiers in Immunology, 2024)
Lung cancer, particularly non-small cell lung cancer (NSCLC), remains a leading cause of cancer-related deaths, with conventional treatments offering limited effectiveness in advanced stages, due to distant metastases and treatment resistance. Recent advancements in immunotherapy, specifically immune checkpoint inhibitors (ICIs), have shown promise, but their efficacy as standalone therapies are often insufficient. This has led to increased interest in combining ICIs with radiotherapy, known as radioimmunotherapy (iRT), to enhance treatment outcomes. This review explores the mechanisms that underlie the synergy between radiotherapy and immunotherapy. Radiotherapy can induce the “abscopal effect”, eliciting systemic immune responses that reduce tumor burdens outside the treated area. It also increases the expression of major histocompatibility complex class I (MHC-I) on tumor cells, improving immune recognition. Furthermore, radiotherapy can modify the tumor microenvironment by inducing metabolic reprogramming to bolster anti-tumor immunity. We discuss strategies for optimizing iRT, including considerations of radiation doses, fractionation schedules, and treatment site selection, which significantly influence immune responses by enhancing MHC-I expression or promoting T-cell infiltration. Clinical evidence supports the efficacy of iRT in NSCLC and other cancers, though challenges in standardizing treatment protocols and managing side effects persist. Overall, radioimmunotherapy presents a promising approach to improving NSCLC treatment outcomes. Ongoing research into its mechanisms and the refinement of treatment may reshape clinical practice, offering more effective and personalized options for patients with advanced lung cancer. Further studies are essential to validate these findings and optimize therapeutic protocols.